Research on the Application of Augmented Reality Technology in the Transformation and Development of Cultural and Creative Industries - Liying, Feng; Ng, Giap Weng; Liyao, Ma; Maozheng, Fu; Xiaoping, Que (European Alliance for Innovation (EAI), 2021)
INTRODUCTION: In this paper, China Hainan "Li" national woven culture is used as an example, the status quo and problems of cultural creative industry in Hainan are analyzed, and the new trend of the development of Hainan cultural creative industry is further clarified. OBJECTIVES: The integration of AR technology and cultural creative industry is the main research object. METHODS: This study integrates technology into culture, introduces AR technology to integrate the development of Hainan cultural and creative industrial development, and propose the transformation strategy of cultural industries to integrate scientific and technological innovation. The application examples of enhanced reality technology are introduced. summarized the four technical characteristics and advantages of AR technology with virtual fusion, real-time interaction, two-way mode and multi-intensity. RESULTS: One preliminary result was Augmented Reality is a promising media to learn, promote and protect Hainan national brocade culture. CONCLUSION: It concludes generally Augmented Reality promotes learning about, and builds back better Hainan's cultural and creative industry.